The threshold elemental ratio of carbon and phosphorus of Daphnia magna and its connection to animal growth - Hamza K. Khattak; Clay Prater; Nicole D. Wagner; Paul C. Frost (2018)
The growth of animal consumers is afected by the balance of elements in their diet with the transition between limitation by one element to another known as the threshold elemental ratio (TER). Precise estimates of TERs with known levels of uncertainty have yet to be generated for most zooplankton consumers. We determined the TER for carbon (C) and phosphorus (P) in for a common lake zooplankter, Daphnia magna, using experimental measurements and theoretical considerations. Daphnia growth responses to food C:P ratios across a relatively narrow range (80–350) generated an empirical estimate of TERC:P of 155±14. While this TER matched our modelled estimate of TERC:P (155±16), it was lower than previous estimates of this dietary transition point. No threshold was found when we examined daphnid body C:N or C:P ratios in response to changing food C:P ratios, which indicates P-limitation at even lower food C:P ratios. Our results provide strong evidence that D. magna is likely to experience acute P-limitation when food C:P ratios exceed even relatively low ratios (~155). Our model further demonstrated that while physiological adjustments may reduce the likelihood of P-limitation or reduce its intensity, these changes in animal material processing would be accompanied by reduced maximum growth rates.